Morphological and molecular pathological features of the breast carcinoma with choriocarcinomatous features: A case report and a literature review - Xu, Jingchun; Xu, Yi; Xu, Cheng; Wang, Cong (Frontiers in Oncology, 2023)
Here we present a rare case of breast cancer with both invasive ductal carcinoma and choriocarcinoma components in a 55-year-old woman. Firstly, the serum human chorionic gonadotropin level showed 15.9mIU/ml preoperatively. And adequate immunohistochemical tests were performed on the specimen. Secondly, High-throughput sequencing was performed to detect the molecular characteristics of the two components, respectively. Then, DNA short tandem repeat (STR) analysis confirmed the homology of the two components, indicating the somatic origin of choriocarcinoma components. Finally, the clinical course and pathological characteristics of the case were reviewed and a literature search for other cases was performed.